Bibliometric profiling of the Philippine Journal of Obstetrics and Gynecology, 2000-2004 - Santos, Cesar Ryan M.; Tarlit, Rodolfo Y. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2007)
This research is about doing a cogitation analysis, author cogitation analysis and bibliographic coupling of the articles of the Philippine Journal of Obstetrics and Gynecology (PJOG) from volumes 24-28 (2000-2004).
The objectives are to determine the organization of the journal, the research fields and trends and most dominant works and authors based on their cogitation and bibliographic counts. Title pages and references were analyzed, and a total of 119 articles and 1,773 citations were encoded using CDS-ISIS for Windows. Only 12 articles were not included in the database because 11 have no cited references and the article Trends and Current Issues in Adult Fecal Incontinence (FI) Towards enhancing the Quality of Life for FI Patients by Matibag, Gino C., M.D., et al (27: 4, October-December 2003) has a publication error. The most popular research topic in PJOG from 2000 to 2004 is cesarean section with 5 citing authors. The widely cited reference in WT Creasman, with 9 citing authors.
Using bibliometric techniques cogitation analysis and bibliographic coupling, the citing authors with the most cogitation link are LSJ Sotto, AM Manalo and GM Limson, cited by Sulay, Raymond, M.D., et al. (2004); Liwag, Arnold, M. D. (2003); Soriano-Cocos, Percida L., M. D., et al. (2002); Zamora, John David, M.D. et al. (2000); and Domingo, Efren M. D. et al. (2000). The most cited work is Gynecologic Oncology for the Clinician with 7 citing authors, and it is closely related to the work Clinical Gynecologic Oncology because the two are both about gynecologic oncology. All of the cited works have bibliographic coupling strengths from 1 to zero.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Philippine Journal of Obstetrics and Gynecology; Bibliographic citations